PENGEMBANGAN TOPO (TRADITIONAL PURIFIER POT) BERBASIS GERABAH BINOH UNTUK MENINGKATKAN KUALITAS FILTRASI AIR RUMAH TANGGA: PENGEMBANGAN TOPO (TRADITIONAL PURIFIER POT) BERBASIS GERABAH BINOH UNTUK MENINGKATKAN KUALITAS FILTRASI AIR RUMAH TANGGA - Nyoman Gema Endra Persada; I Gusti Ayu Wulan Krisna Dewi; Putu Surya Triana Dewi; Ardina Susanti (Bangun Rekaprima, 2026)
The availability of clean water is a serious challenge amidst rapid urbanization, environmental pollution, and climate change, especially in Bali. This condition is exacerbated by limited access to PDAM (Regional Water Company) and the declining quality of ground and surface water. This research developed TOPO (Traditional Purifier Pot), a household water filter device based on traditional pottery from Sentra Binoh, North Denpasar. TOPO is designed as a solution for providing clean water that is affordable, environmentally friendly, while also elevating local Balinese values ​​through functional and aesthetic design. The research method combines qualitative and quantitative approaches, including literature studies, observations, interviews, and laboratory tests on well water quality before and after filtration using a pottery filter made of clay and paras powder. Test parameters include physical, chemical, and microbiological aspects referring to Minister of Health Regulations No. 2 of 2023 and No. 66 of 2014. The results show that the pottery filter is able to reduce contaminant levels significantly, although some elements such as manganese still exceed the safe threshold. Therefore, TOPO is more appropriate for use as a container for raw water that is boiled before consumption. The TOPO design was developed through an ATUMICS approach, using the metaphor of the turtle as a symbol of balance, sustainability, and the water element in Balinese culture.